Internalisasi Nilai-Nilai Akhlakul Karimah pada Pelajar MA NW Putra Narmada sebagai Upaya Pencegahan Perilaku Cyberbullying - Muh. Asroruddin al Jumhuri; Fatmawati; Andrian Firdaus (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
The rapid development of information technology and social media has transformed student interaction patterns while giving rise to a new form of violence known as cyberbullying. This phenomenon not only affects public schools but has also extended to Islamic-based schools (madrasahs). This community service program aims to internalize the values of noble character (akhlakul karimah) among students of Madrasah Aliyah Nahdlatul Wathan (MA NW) Putra Narmada as a preventive measure against cyberbullying behavior. The study employed a descriptive qualitative approach with execution methods comprising initial observation, socialization, training, exemplary-based coaching (uswah hasanah), habituation, and mentoring. Data were collected through participatory observation, in-depth interviews with the school principal, Akidah Akhlak (Islamic Ethics) teachers, and student representatives, as well as document analysis. The data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and drawing conclusions. The results indicated that prior to the intervention, students' understanding of social media etiquette limits from an Islamic perspective was low, as evidenced by habits of making harsh comments, sharing screenshots, and teasing one another in online group chats. Following the internalization of akhlakul karimah values—such as positive thinking (husnuzan), truth verification (tabayyun), guarding the tongue (hifzhul lisan), and avoiding backbiting (ghibah) and tale-bearing (namimah)—there was an increase in awareness and a shift in student attitudes toward more responsible social media usage. The internalization process proved most effective when combining three approaches: teacher role-modeling, habituation through daily religious activities, and reinforcing comprehension through contextualized Akidah Akhlak learning suited to digital realities. This program concludes that akhlakul karimah values rooted in the Quran and Hadith serve as a relevant and applicable moral foundation for fostering civilized student character in the digital space. It is recommended that similar programs be continued sustainably and integrated into the curriculum and school culture.